1997
DOI: 10.1002/(sici)1520-6572(199721)3:1<43::aid-sess4>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing children's distress during medical procedures

Abstract: Medical fears are common in children and can have long‐term implications for future attitudes toward health care. Providing accurate information about an impending medical procedure can help the inexperienced child prepare for a painful or unpleasant medical experience and ultimately adapt to the experience more rapidly. The main strategies for providing developmentally appropriate medical information to children are reviewed, and common errors made by parents and medical staff are highlighted. However, anxiou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…(Packman et al) Once it is determined that the pediatric sibling donor is fit to undergo the donation procedure, the PCP may have a significant role in decreasing the child's stress and anxiety about the impending donation. In a study pertaining to children's distress during medical procedures, Dahlquist (1997) showed that fearsome events are perceived as less uncomfortable and are adapted to more quickly by children when they are predictable. Providing accurate and age-appropriate information about the impending procedure may also help the child prepare for the experience and adapt to it more rapidly.…”
Section: Implications For the Primary Care Providermentioning
confidence: 99%
See 1 more Smart Citation
“…(Packman et al) Once it is determined that the pediatric sibling donor is fit to undergo the donation procedure, the PCP may have a significant role in decreasing the child's stress and anxiety about the impending donation. In a study pertaining to children's distress during medical procedures, Dahlquist (1997) showed that fearsome events are perceived as less uncomfortable and are adapted to more quickly by children when they are predictable. Providing accurate and age-appropriate information about the impending procedure may also help the child prepare for the experience and adapt to it more rapidly.…”
Section: Implications For the Primary Care Providermentioning
confidence: 99%
“…Providing accurate and age-appropriate information about the impending procedure may also help the child prepare for the experience and adapt to it more rapidly. This information increases the predictability of frightening medical procedures, thereby increasing the probability of a less stressful experience and a more rapid recovery (Dahlquist, 1997). Additional potential benefits of providing accurate and effective information about an impending procedure include fostering trust, reducing uncertainty, enhancing a child’s belief in his or her ability to cope with a procedure, minimizing distress, optimizing outcomes and recovery time, and minimizing pain (Jaaniste, Hayes, & von Baeyer, 2007).…”
Section: Implications For the Primary Care Providermentioning
confidence: 99%